Building integrated connections for children, their families and communities - Brettig, Karl.; Sims, Margaret (Newcastle : Cambridge Scholars, 2011)
Research and practice shows that many vulnerable children and families face more than one challenge and require more than one intervention. However our service system has evolved historically to deal with one thing at a time or to provide services from multiple sources. This lack of integration can have a devastating effect on some families where key information or warning signs are missed. Coronial and judicial inquiries constantly stress the negative impact of a 'siloed' approach to service ...
THE CHALLENGES OF THE EAST KIMBERLEY EXPERIENCE IN COLLABORATION AND SUSTAINABILITYDRIVING SYSTEM CHANGE TO SUPPORT VULNERABLE CHILDREN AND THEIR FAMILIES; CHAPTER TWELVE; CONTRIBUTORS; INDEX OF CHAPTER SUB-HEADINGS.
Selected conference papers.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Social work administration -- Congresses; Family social work -- Congresses; Dysfunctional families -- Services for -- Congresses; Abused children -- Services for -- Congresses; Service social -- Gestion -- Congrès.; Service social familial -- Congrès.; Social welfare & social services; Child welfare; Child care & upbringing; SOCIAL SCIENCE -- Social Work; Abused children -- Services for; Dysfunctional families -- Services for; Family social work; Social work administration; Conference papers and proceedings